Integrable NLS equation with time-dependent nonlinear coefficient and self-similar attractive BEC - Kraenkel, Roberto André [UNESP]; Nakkeeran, K.; Chow, K. W. (Elsevier B.V., 2011)
We investigate the nonlinear Schrodinger equation with a time-dependent nonlinear coefficient. By means of Painleve analysis we establish the integrability for a particular form of the nonlinear coefficient. The corresponding soliton solution is shown to be of the self-similar kind. We discuss the implications of the result to the dynamics of attractive Bose-Einstein condensates under Feshbach-managed nonlinearity and explore the possibility of a managed self-similar evolution in 1D condensates. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Nonlinear Schrodinger equation; Bose-Einstein condensate (BEC); Soliton; Hirota bilinear method